¿Volver a ser español ? Los descendientes franceses de exiliados republicanos y la posible recuperación de la nacionalidad de sus ascendientes - Evelyne Ribert (Cahiers de Civilisation Espagnole Contemporaine)
The so-called Historical Memory Act (2007), which aims to recognize the victims of Francoism, has allowed the descendants of Spanish republican exiles to acquire or recover the Spanish nationality, of which they or their ascendants were deprived. After presenting the law briefly, this article, drawing on an survey of descendants of exiles residing in France, analyzes the significance that the acquisition of Spanish nationality may have for the children and grandchildren of exiled Spanish republicans. This appears, depending on the cases, as an attempt to compensate for a loss or a form of reconciliation with Spain. The motivations of the descendants of exiles residing in Latin America, who nearly 95% of the applicants, seem to be different, amalgamating practical considerations and symbolic considerations.